The Future of Shopping: Traditional Patterns and Net Effects - Markham, Julian E (Wiltshire, UK Macmillan Press, 1998)
In many countries shopping has been transformed from High Street stores to large out-of-town Retail Parks and Shopping Centres. Technology now provides the opportunity for many products and services to be promoted and purchased electronically, particularly via the Internet. This will progress differently for different products, regions, consumer groups, etc. This book presents future scenarios for the retail industry in the light of Internet shopping. Through its unique perspective, it examines developments so far, and through the insight of the author who is one of the leading professionals in shopping centre developments, takes an inspired look at the future of retailing in the next century.
Age Group: Adult
Includes bibliographical references (p. 230-234)
Keywords: Shopping; Teleshopping